The Relationship Between The Level Of Protein And Carbohydrate Adequacy, The Activity Of Weighing, The Level Of Maternal Knowledge With Nutritional Status In Toddlers Aged 12-59 Months In Ulak Rengas Village, Abung Tinggi Sub-District, North Lampung District - Archela, Rara Qory; Muharramah, Alifiyanti; Abdullah, Abdullah; Khairani, Masayu Dian (INDOGENIUS, 2025)
Background & Objective: Nutritional status is a reflection of the size of the fulfillment of nutritional needs obtained from the intake and use of nutrients by the body. One of the factors that affect nutrition in toddlers is the level of parental education. The purpose of this study was to determine the relationship between the level of protein and carbohydrate adequacy, the activeness of weighing, the level of maternal knowledge with nutritional status in toddlers aged 12-59 months in Ulak Rengas Village, Abung Tinggi District, North Lampung Regency in 2024. Method: The type of research used was quantitative with a cross sectional design. Data collection was done by interview using a structured questionnaire and 2x24 hour food recall. The population in this study were mothers and toddlers 12-59 months, while the samples taken were 44 mothers and toddlers. Bivariate analysis in this study used the Gamma test. Result: The results obtained ρ value 0.001 < 0.05 which means there is a relationship between the level of protein adequacy with the nutritional status of toddlers aged 12-5h9 months, ρ value <.001 < α (0.05) there is a relationship between the level of carbohydrate adequacy with the nutritional status of toddlers aged 12-59 months, ρ value 0.854 < α (0.05) there is no relationship between weighing activity with the nutritional status of toddlers aged 12-59 months, the results of ρ value 0.854 < α (0.05) there is a relationship between the level of maternal knowledge with the nutritional status of toddlers aged 12-59 months. Conclusion: Answering the research objectives. Should consist of There is a relationship between the level of maternal knowledge and the nutritional status of toddlers aged 12-59 months.